Intelligent Systems in The Management of Regional Resources: Benefits for Sustainable Development - Melnychenko , Svitlana; Cholyshkina , Olga; Rtyshchev, Serhii; Mishchenko , Alla; Karpinskyi , Roman (Studia Ecologiae et Bioethicae, 2024)
The purpose of our research is to analyse intelligent systems, identify their key features in general and in the context of regional resource management in particular; to provide a detailed list of the main intelligent technologies and systems used in regional resource management and the areas of their direct use. The main emphasis should be placed on the benefits of using intelligent systems in the management of regional resources in the context of sustainable development as well as on the problems that can be overcome through the use of intelligent systems. The study should also analyse the negative aspects of the use of intelligent systems in regional resource management. In order to achieve this goal, the general philosophical method, the method of system analysis, synthesis, deduction and induction, dialectical method and formal legal method were used. The findings of the study will serve as a basis for further research and a catalyst for increasing the use of smart technologies, taking into account all the benefits and potential risks.